Influence of hydroxyapatite coating thickness and powder particle size on corrosion performance of MA8M magnesium alloy - Sonmez, S.; Aksakal, B.; Dikici, B. (ELSEVIER SCIENCE SA, 2014)
To improve the corrosion resistance of MA8M magnesium alloy, sol-gel derived coatings of micron and nano-scale hydroxyapatite (HA) were coated successfully on MA8M magnesium alloy substrates. The effects of coating thickness and HA powder particle size on the adhesion strength and corrosion resistance on magnesium alloy was investigated. Potentiodynamic polarization (PDS) tests were performed in a Ringer solution. The coatings before and after corrosion tests were characterized by adhesion tests, scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis. The results show that the micro-scale-HA coated Mg substrates were more corrosion resistant than the nano-scale-HA coatings. Corrosion susceptibilities of the nano-scale-HA coated samples were influenced inversely. The anodic activity of the micro-scale-HA coatings increased with increased coating thickness. The coated film provided good barrier characteristics and achieved good corrosion protection for Mg substrates when compared to substrates without any coatings. The best corrosion resistance was obtained at 30 mu m film thickness for micro-scale-HA coatings. (C) 2014 Elsevier B. V. All rights reserved.
Keywords: Magnesium alloy; Coating; Hydroxyapatite; Corrosion; IN-VIVO CORROSION; AZ31; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering